CONSERVATION DEVELOPMENT OF TIMOR DEER (Cervus timorensis) AS COMMERCIAL PURPOSE(WITH OPTIMISTIC RATE ESTIMATION) - Santoso, S.I.; Fanani, Z.; Nugroho, B.A.; Hanani, N. (Diponegoro University, 2012)
The aim of this research was to determine the profit obtained from breeding of Timor deercommercially. This research was done in East Java. Survey method was used to answer the objective.The study location were selected by purposive sampling. Usually deer was develop in conservation area,but because the area was decrease so the number of deer also decrease. Model of deer raisingdevelopment should be improved not only for conservation but also for commercial purpose. Theoptimum deer raising were considered and monitored with a purpose to maximize commercial Timordeer by using Multiple Objective Goal Programming (MOGP) to find the Optimistic Rate Estimation.The result of this study showed to get the optimum benefit, it had to be applied together withconservation and commercial effort at the same time. Results of study showed that profit was taken fromselling velvet was 164.46%. Profits taken from selling antler was 350.56%, from selling alive deer was394.28%, from selling recreation tickets was 259.08%, from selling venison1 was 135.98%, and fromselling deer leather was 141.24%. Operational cost spent were 168.46% for feeding cost, 213.23% formaintenance cost, and 232.04% for labors’ salaries. The amount of operational cost required in MOGPmodel, with lower expenses and commercial priority were 185.54% for feeding cost, 253.13% formaintenance cost, and 246.95% for paying labors’ salaries. The MOGP model result with commercialpriority reached 335.21%, while in MOGP model with lower costs and commercial priority gave profitfor breeders up to 381.26%.